Analisis Penanggulangan Kemiskinan Melalui Program Keluarga Harapan (PKH) Studi Kasus Desa Ladang Tuha Kecamatan Meukek Kabupaten Aceh Selatan - Nurjalia nurjalia; Leli Putri Ansari leli (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to analyze poverty alleviation through the Family Hope Program (PKH) with a case study of Ladang Tuha Village, Meukek District, South Aceh Regency. This research is a descriptive qualitative research using primary data where the data is obtained from interviews. The population is the PKH recipient community in Ladang Tuha Village, Meukek District, South Aceh Regency as many as 49 people consisting of 21 families and the total sample is taken from the total population. Sampling uses total sampling where all the population is sampled. Based on the results of the study, it was shown that PKH in Ladang Tuha Village, Meukek District, South Aceh Regency was effective, but the criteria for PKH recipients in the previous year in Ladang Tuha Village were more varied, namely pregnant women, the elderly, and disabled. Meanwhile, in 2022 only toddlers and school children will receive PKH. The amount of PKH money did not come out on time. The Prosperous Family Card is often blocked by itself so that PKH recipients cannot withdraw money until two withdrawals are made before being able to withdraw money back. PKH participants must report to the PKH district level administrator to be able to be unblocked again by the PKH management. Furthermore, the advice given is that it is hoped that in the future PKH in Ladang Tuha Village, Meukek District, South Aceh Regency that PKH money can be released on time and information is more transparent.